Domains relating to the everyday impact of hearing loss, as reported by patients or their communication partner(s): protocol for a systematic review - Vas, Venessa; Akeroyd, Michael A.; Hall, Deborah A. (BMJ Publishing Group Ltd, 2016)
INTRODUCTION: Hearing loss is a highly prevalent condition that affects around 1 in 6 people in the UK alone. This number is predicted to rise by the year 2031 to a staggering 14.5 million people due to the ageing population of the UK. Currently, the most common intervention for hearing loss is amplification with hearing aid(s) which serve to address the issue of audibility due to hearing loss, but cannot reverse its effects. The consequences of hearing loss are multifaceted, as it is a complex condition that can detrimentally affect various aspects of an individual's life, including communication and personal relationships. The scope of these reported issues is so broad that it calls on the need for patient-centred management plans that are tailored to each patient as well as appropriate measures to assess intervention benefit. It is unclear whether current outcome instruments adequately match what patients report as the most important problems for them.